Pelaksanaan Mulok Bahasa Lampung dalam Upaya Pelestarian Bahasa Lampung di Kabupaten Lampung Selatan - Ratih Rahayu (Kantor Bahasa Lampung, 2020)
This study describes the conditions of the implementation of the Lampung language mulok in the effort to preserve the Lampung language and what efforts have been made by the local government in the context of their development and development. This study was conducted in South Lampung Regency. The results of this study are expected to be useful to find out the conditions of the implementation of the Mulok Lampung language in South Lampung Regency and what efforts have been made by the local government in the context of fostering regional languages. Based on the results of the study it can be concluded that the Mulok language in Lampung has sufficiently increased students 'positive attitudes towards regional languages as well as increasing students' knowledge and skills. However, the implementation of the Lampung language mulok in South Lampung Regency experienced several obstacles that needed improvement in several parts. Lampung language teaching as a local content that aims for students to have basic knowledge and skills to communicate using language that is good and right in accordance with the language and spelling of Lampung needs to be improved through curriculum improvement and improving the quality and welfare of teachers. AbstrakKajian ini menjabarkan kondisi pelaksanaan mulok bahasa Lampung dalam upaya pelestarian bahasa Lampung serta upaya apa yang telah dilakukan pemerintah daerah dalam rangka pembinaan dan pengembangannya. Kajian ini dilaksanakan di Kabupaten Lampung Selatan. Hasil kajian ini diharapkan dapat bermanfaat untuk mengetahui kondisi pelaksanaan mulok bahasa Lampung di Kabupaten Lampung Selatan serta upaya apa saja yang telah dilakukan oleh pemerintah daerah dalam rangka pelestarian bahasa daerah. Berdasarkan hasil kajian maka dapat disimpulkan bahwa mulok bahasa Lampung telah cukup meningkatkan sikap positif siswa terhadap bahasa daerah juga menambah pengetahuan dan keterampilan peserta didik. Namun demikian, pelaksanaan mulok bahasa Lampung di Kabupaten Lampung Selatan mengalami beberapa kendala yang perlu perbaikan di beberapa bagian. Pengajaran bahasa Lampung sebagai mulok yang bertujuan agar peserta didik memiliki pengetahuan dan keterampilan dasar berkomunikasi menggunakan bahasa yang baik dan benar sesuai dengan lafal dan ejaan bahasa Lampung perlu ditingkatkan melalui perbaikan kurikulum dan peningkatan kualitas serta kesejahteraan guru.